Archipelago's Strategy in the Authentic Culinary Banyumas Video Clip (Visual and Cultural Aesthetic Analysis) - Ferdinanda Ferdinanda; Galih Putra Pamungkas; Riri Irma Suryani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The existence of traditional culinary is now starting to be difficult to find in the community, including traditional culinary Banyumas, which has a variety of traditional cuisine, including Gethuk Goreng, Lanting, Nopia, Soto Sokaraja, Jenang Jaket or Wajik Klethik, Kraca, Mendoan Banyumas, Jalabiya, Intil, Badeg, Soft and a variety of other traditional foods and drinks. As a generation that is close to technology and information, culinary producers must of course focus on the younger generation segment as their target. This is also supported by the presence of social media which facilitates the distribution of information to target consumers. The video clip titled Banyumas Authentic Culinary (BAC) is a 2-minute video circulating on social media Instagram. This clip was first published in mid-September 2021, and was able to attract more than 20,000 viewers within 3 days of being published. BAC focuses more on visualizing details of several traditional Banyumas culinary specialties. The BAC video will be analyzed descriptively in dark and light colors, contrast guides, rhythm guides, creativity theory, aesthetic form theory, and cultural integration.